Evaluation of the genetic variability of homoeologous group 3 SSRs in bread wheat - Chebotar, S.; Sourdille, P.; Paux, E.; Balfourier, F.; Feuillet, C.; Bernard, M. (Цитология и генетика, 2009)
Thorough characterization of the genetic variability in bread wheat (Triticum aestivum L.) is important for a better improvement of this key crop and to increase cereal yield in the context of sustainable agriculture to face human needs in the next decades. To study the genetic variability of SSRs on wheat homoeologous group 3 chromosomes, we characterized 38 hexaploid and two tetraploid wheat lines using a set of 165 microsatellites that we cytogenetically assigned to the 17 deletion bins for chromosomes group 3.